Bacterial aerobic synthesis of nanocrystalline magnetite - Bharde, Atul A.; Wani, A.; Shouche, Y.; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Journal of the American Chemical Society, 2005)

Cobalt and magnesium ferrite nanoparticles: preparation using liquid foams as templates and their magnetic characteristics - Bala, Tanushree; Sankar, C. R.; Baidakova, Marina; Osipov, V.; Enoki, Toshiaki; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Langmuir, 2005)
An easy and convenient method for the synthesis of cobalt and magnesium ferrite nanoparticles is demonstrated using liquid foams as templates. The foam is formed from an aqueous mixture of an anionic surfactant and the desired metal ions, where the metal ions are electrostatically entrapped by the surfactant at the thin borders between the foam bubbles and their junctions. The hydrolysis is carried out using alkali resulting in the formation of desired nanoparticles, with the foam playing the role of a template. However, in the formation of ferrites with the formula MFe2O4, where the metal ion and iron possess oxidation states of +2 and +3, respectively, forming a foam from a 1:2 mixture of the desired ionic solutions would lead to a foam composition at variance with the original solution mixture because of greater electrostatic binding of ions possessing a greater charge with the surfactant. In our procedure, we circumvent this problem by preparing the foam from a 1:2 mixture of M2+ and Fe2+ ions and then utilizing the in situ conversion of Fe2+ to Fe3+ under basic conditions inside the foam matrix to get the desired composition of the metal ions with the required oxidation states. The fact that we could prepare both CoFe2O4 and MgFe2O4 particles shows the vast scope of this method for making even multicomponent oxides. The magnetic nanoparticles thus obtained exhibit a good crystalline nature and are characterized by superparamagnetic properties. The magnetic features observed for CoFe2O4 and MgFe2O4 nanoparticles are well in accordance with the expected behaviors, with CoFe2O4 particles showing higher blocking temperatures and larger coercivities. These features can easily be explained by the contribution of Co2+ sites to the magnetocrystalline anisotropy and the absence of the same from the Mg2+ ions.

Gold nanoparticle networks with photoresponsive interparticle spacings - Sidhaye, D. S.; Kashyap, Sudhir; Sastry, M.; Hotha, Srinivas; Bhagavatula L. V. Prasad (Langmuir, 2005)
Photoresponsive gold nanoparticle networks were prepared by functionalizing them with azobenzene derivatives. A network can be formed when a linker molecule constituting the azobenzene moiety suitably derivatized on either side with gold surface sensitive groups such as thiols and amines is added to the nanoparticle solution. It is shown that the interparticle spacing in the networks could be controlled by the reversible trans-cis isomerization of the azobenzene moiety induced by UV and visible light, respectively. The photoinduced variation in the interparticle spacings is inferred by the changes in the optical spectra of the gold nanoparticles which display a red or blue shift in the surface plasmon resonance peak depending on a decrease or increase in the interparticle spacing, respectively. Transmission electron microscopy images are in consonance with the evidence from the optical spectra.

Novel method for the synthesis of siloxane nanowires and filaments using gold nanoparticle catalysts - Bhagavatula L. V. Prasad; Stoeva, S.; Sorensen, C. M.; Klabunde, Kenneth J.; Zaikovskii, V. (International Conference on Nanoscience and Technology, 2005)
A unique polymerization reaction of alkylsilanes to siloxane nanowires, filaments and tubes in presence of gold nanoparticles and water is presented. The gold nanoparticles, which catalyze this reaction also work as templates restricting the shape of the resulting polymers into wires and tubes. High resolution transmission electron microscopy images clearly reveal the presence of gold nanoparticle at the tip of each wire supporting the template hypothesis. Elemental analyses by different methods confirm the stoichiometry to be C18H37SiO1.5, when the alkylsilane used was C18H37SiH3, thus proving that the alkyl group remains intact during the polymerization reaction.
Keywords: gold nanoparticles; Nanowires; siloxane polymers

Phase transfer of oleic acid capped NicoreAgshell nanoparticles assisted by the flexibility of oleic acid on the surface of silver - Bala, Tanushree; Swami, A.; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Colloid and Interface Science, 2005)
The phase transfer protocols in vogue for the oleic acid capped silver nanoparticles, viz., salt-induced precipitation and redispersion or phosphoric acid-induced method, are examined and compared thoroughly. A comprehensive evaluation with respect to the mechanistic aspects involved is made and the merits and demerits of the different procedures are delineated. It is found that the salt-induced precipitation and redispersion is more versatile in that the precipitate can actually be redispersed in both aqueous and organic media. However, in terms of mechanism both the routes seem to be very similar wherein the orientational change of oleic acid on the silver surface in the two different environments-organic and aqueous-plays a crucial role in the adaptability of the system to the different environments. Subsequently, this change of orientation of oleic acid on silver surface in aqueous and organic media has been utilized to phase transfer Ni-based nanoparticulate systems. The nascent oleic acid-capped Ni nanoparticles, which were synthesized by a foam-based protocol, were dispersible in water but not in nonpolar organic media such as cyclohexane or toluene. Then, just by coating a thin shell of silver on them we could achieve complete phase transfer of the NicoreAgshell from aqueous to organic media following similar procedures used for oleic acid-capped silver nanoparticles. Here, the phase transfer seems to be facilitated by the orientational flexibility of oleic acid on the silver surface as opposed to other metal surfaces as evidenced from the infrared and thermogravimetric analyses of oleic acid-capped Ni and NicoreAgshell nanoparticles. This orientation-assisted phase transfer method could be generalized and can be adapted to other systems where, if the nascent nanoparticles cannot be phase transferred as is, they can be coated by a silver shell and oleic acid making them suitable for dispersion in both aqueous and organic media. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: (1) HNMR; FTIR; Phase transfer; transmetalation core-shell nanoparticles; UV-Vis

Reversible transformations of gold nanoparticle morphology - Stoeva, Savka I.; Zaikovski, Vladimir; Bhagavatula L. V. Prasad; Stoimenov, Peter K.; Sorensen, Christopher M.; Klabunde, Kenneth J. (Langmuir, 2005)
Herein is reported a metamorphosis taking place in a gold nanosized system. The observed phenomenon of shape and size transformations was found to be completely reversible. Unlike most procedures in the literature where shape and size control occur in the synthetic step by adding growth- and shape-controlling agents such as surfactants or polymers, in this system postsynthetic changes in shape and size can be carried out simply by changing the ratio of reactive, competing reagents, more specifically, alkylthiols versus tetralkylammonium salts. Interestingly, the transfer of gold metal occurs (large prismatic particles to small particles and vice versa) under the influence of reagents that do not cause such interactions with bulk gold. All intermediate steps of the morphology change were observed using HRTEM and electron diffraction. The processes of breaking down and “welding back” solid metal nanoparticles occur under mild conditions and are remarkable examples of the unique chemical properties of nanomaterials. The described process is expected to be relevant to other nanoscale systems where similar structural circumstances could occur.

Solvent-adaptable silver nanoparticles - Bhagavatula L. V. Prasad; Arumugam, S. K.; Bala, Tanushree; Sastry, M. (Langmuir, 2005)
A simple and efficient way of obtaining silver nanoparticles that are dispersible both in organic and in aqueous solvents using a single capping agent is described. The silver nanoparticles are initially prepared in water in the presence of aerosol OT [sodium bis(2-ethylhexyl)-sulfosuccinate, AOT]. Thereafter, transfer of the AOT-capped silver nanoparticles to an organic phase is induced by the addition of a small amount of orthophosphoric acid during shaking of the biphasic mixture. The AOT-stabilized silver nanoparticles could be separated out from the organic phase in the form of a powder. The hydrophobic nanoparticles thus prepared are stable and are readily resuspended in a variety of other polar (including water) and nonpolar solvents without further surface treatment. The amphiphatic nature of the silver surface is brought about by a small orientational change in the AOT monolayer on the silver surface in response to the polarity of the solvent.

Synthesis of gold, silver and their alloy nanoparticles using bovine serum albumin as foaming and stabilizing agent - Singh, A. V.; Bandgar, B. M.; Kasture, Manasi; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Materials Chemistry, 2005)
A simple and convenient method for the synthesis of gold, silver and their alloy nanoparticles in a foam matrix using the protein bovine serum albumin (BSA) is reported. BSA is an excellent foaming agent and, by virtue of its zwitterionic character at the protein isoelectric point, may be used to bind to either cationic silver (Ag+) or anionic gold (AuCl4-) ions in the foam. The metal ions in the foam are thereafter reduced in situ to yield silver and gold nanoparticles. The versatility of an amphoteric foaming agent is further demonstrated by the simultaneous binding of Ag+ and AuCl4- ions with zwitterionic BSA leading to the possibility of obtaining Au-Ag alloy nanoparticles in the foam. The BSA molecules coat and stabilize the nanoparticles thus prepared eliminating the necessity of employing an additional stabilizing agent in the experimental recipe.

Assembly of phase transferred nickel nanoparticles at air-water interface using Langmuir-Blodgett technique - Bala, Tanushree; Joshi, Bhagyashree; Iyer, Neelima; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2006)
Development of simple and efficient protocol for the synthesis of Ni nanoparticles in aqueous media and their subsequent phase transfer to organic media is reported. The synthesis of nickel nanoparticles in aqueous medium is accomplished by reducing the nickel nitrate with sodium borohydricle in presence of oleic acid. It results in the formation of nickel nanoparticles capped with oleic acid. The pristine oleic acid capped nickel nanoparticles were then phase transferred to nonpolar solvents such as toluene using stearic acid. The phase transfer was effective probably due to the space exchange between the oleic acid moiety and stearic acid molecules. The hydrophobized Ni thus obtained was organized at the air-water interface and it was observed that by controlling the pressure and concentration of hydrophobized Ni nanoparticles at air-water interface, linear ribbon like assemblies could be obtained. The organization process was followed by surface pressure-area isotherm measurement and Brewster Angle Microscopy.
Keywords: assembly; Langmuir-Blodgett technique; Ni nanoparticles; Phase transfer

La0.7Sr0.3MnO3 nanoparticles coated with fatty amine - Rajagopal, Rajashree; Mona, J.; Kale, Sangeeta N.; Bala, Tanushree; Pasricha, Rem; Poddar, P.; Sastry, M.; Bhagavatula L. V. Prasad; Kundaliya, Darshan C.; Ogale, S. B. (Applied Physics Letters, 2006)
We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30 rim. The process involves citrate-gel synthesis, size filtering, and; surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of similar to 360 K establishing the desired stoichiometry and phase. Fourier transform infrared-studies bring out. that the amine group of ODA interacts with the LSMO surface. Refluidization yields uniform redispersion of the coated and dried powder. (c) 2006 American Institute of Physics.

Controlled aggregation of gold nanoparticle networks induced by alkali metal ions - Tamang, Sudarsan; Hotha, Srinivas; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
Gold nanoparticle networks were obtained by linking them with cysteine modified triethyleneglycols. The oligo-ether linker molecule initially having a linear structure probably adopts a crown ether type structure upon complexation with alkali metal ions that leads to a controlled aggregation of the network. The extent of aggregation depends on the degree of conformational change in the molecule upon complexation with the metal ion, which in turn is governed by the metal ion radius leading to a dependence of red shift of the surface plasmon resonance on the metal ion radius. Since this network is present in the organic solvent they also act as phase transferring agent for the alkali metal ions from aqueous to organic media.
Keywords: Aggregation; Alkali Metal Ions; Au Nanoparticles; Crown Ether; Surface Plasmon Resonance

Effect of halogen addition to monolayer protected gold nanoparticles - Singh, Sanjay; Pasricha, Renu; Bhatta, Umananda M.; Satyam, P. V.; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2007)
The effects of N-halosuccinimide and halogen addition to monolayer protected gold nanoparticles (Au NPs) dispersed in organic media are described. Contrary to the expectation that nanoparticles dispersed in organic media are stable against aggregation, N-iodosuccinimide addition induced aggregation of octadecylamine capped gold nanoparticles in chloroform or toluene. It was observed that even KI and CuI addition could bring about the aggregation though they are very sparingly soluble in organic solvents. It was also found that even molecular iodine could bring about the above mentioned aggregation. Interestingly, when CuI is used the aggregated structures readily convert to very thin flat nanostructures upon exposure to an electron beam or UV irradiation. In fact when the aggregation is induced by the addition of KI or N-iodosuccinamide we do not see the flattening of the aggregated structures exemplifying the important role of Cu ions in making these flat structures.

Ferromagnetic resonance in nanomagnetic metal core and noble metal shell systems - Bala, Tanushree; Enoki, Toshiaki; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
The change in the line widths in the ferromagnetic resonance (FMR) spectra of Co and Ni nanoparticles upon shell formation with noble metals like gold or silver are described. The NicoreAgshell, CocoreAgshell, and CocoreAushell nanoparticles were prepared by a simple transmetallation reaction between the Co and Ni nanoparticles and the Ag+ or AuCl−4 ions. It is revealed that the FMR line width decreases upon Ag shell formation whereas it increases upon core–shell composite formation with Au. Several probable explanations such as the differences in size distributions before and after the reaction or the changes occurring in shape anisotropy of the particles due to the shell formation or the different extents of electronic interaction between the core and shell materials have been offered for this observation.
Keywords: Fmr Study; Line Width Comparison; Magnetic Core-Noble Metal Shell Nanoparticles

Interaction of different metal ions with carboxylic acid group: a quantitative study - Bala, Tanushree; Bhagavatula L. V. Prasad; Sastry, Murali; Kahaly, Mousumi Upadhyay; Waghmare, Umesh V. (Journal of Physical Chemistry A, 2007)
The binding strength of the carboxylic acid group (-COOH) with different divalent metal ions displays considerable variation in arachidic acid (AA) thin films. It is considered that in AA thin films the metal ions straddle the hydrophilic regions of the stacked bilayers of AA molecules via formation of carboxylates. In this study first the uptake of different divalent cations in films of AA is estimated by atomic absorption spectroscopy (AAS). Through the amount of cation uptake, it is found that the strength of binding of different cations varies as Ca2+ > Co2+ > Pb2+ > Cd2+. Variation in the binding strength of different ions is also manifested in experiments where AA thin films are exposed to metal ion mixtures. The higher binding strength of AA with certain metal ions when exposed individually, as well as the preference over the other metal ions when exposed to mixtures, reveal some interesting deviation from the expected behavior based on considerations of ionic radii. For example, Pb2+ is always found to bind to AA much more strongly than Cd2+ even though the latter has smaller ionic radius, indicating that other factors also play an important role in governing the binding strength trends apart from the effects of ionic radii. Then, to get a more meaningful knowledge regarding the binding capability, first-principles calculations based on density functional theory have been applied to study the interaction of different cations with the simplest carboxylic acid, acetic acid, that can result in formation of metal diacetates. Their electronic and molecular structures, cohesive energies, and stiffness of the local potential energy well at the cation (M) site are determined and attempts are made to understand the diversity in geometry and the properties of binding of different metal ions with -COOH group. We find that the calculated M−O bond energies depend sensitively on the chemistry of M atom and follow the experimentally observed trends quite accurately. The trends in M−O bond energies and hence the total M−acetate binding energy trends can actually be related to their molecular structures that fall into different categories:  Ca and Cd have tetrahedral coordination; Fe, Ni, and Co exhibit planar 4-fold coordination; and Pb is off-centered from the planar structure (forming pyramidal structure) due to its stereochemically active lone pair of electrons.

Magnetic transition and large magnetocaloric effect associated with surface spin disorder in Co and CocoreAgshell nanoparticles - Poddar, P.; Srinath, S.; Gass, James; Bhagavatula L. V. Prasad; Srikanth, H. (Journal of Physical Chemistry C, 2007)
We report a reversible, large magnetocaloric effect in the vicinity of a low-temperature magnetic transition in Co and CocoreAgshell nanoparticles synthesized using a wet chemical method. The as-synthesized assembly of the particles shows a sharp low-temperature peak in the zero-field-cooled (ZFC) magnetization well below the blocking transition temperature, and this feature is associated with the surface spin disorder. Co nanoparticles show a large increase in the magnetic entropy at around 15 K with a peak value of nearly 2.25 J/K center dot kg for an applied field of 30 kOe. A similar trend is also observed in the silver-coated Co particles. These are some of the largest NICE values observed in nanoparticles to date. The features are ascribed to the low-temperature spin-glass-like freezing transition associated with the surface spins in the shell region that is distinct from the behavior of core spins. Our studies reveal that manipulating the surface anisotropy in core-shell nanoparticles has the potential to lead to a large NICE effect and thus prove to be useful for magnetic refrigeration.

Multiutility sophorolipids as nanoparticle capping agents: synthesis of stable and water dispersible Co nanoparticles - Kasture, Manasi; Singh, Sanjay; Patel, Pitamber; Joy, Pattayil Alias; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (Langmuir, 2007)
Sophorolipids are a class of glycolipids that can be obtained from fatty acids by simply treating them with yeast cells (Candida bombicola, ATCC 22214) and glucose. In this letter, we demonstrate the application of sophorolipids obtained from oleic acid as a capping agent for Co nanoparticles. Upon capping the nanoparticle surface, the sugar moiety of these sophorolipids is exposed to the solvent environment, making the nanoparticles stable and water-redispersible.

Nearly complete oxidation of Au(0) in hydrophobized nanoparticles to Au(3+) ions by N-bromosuccinimide - Singh, Sanjay; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2007)
Au degrees atoms in hydrophobized gold nanoparticles were oxidized to Au(3+) ions, nearly quantitatively, simply by treatment with N-bromosuccinimide and sonication. (1)H NMR results indicate that the octadecylamine molecules are detached from the Au degrees surface by NBS. The bromine molecules released by NBS are suggested to be the species responsible for the oxidation of Au degrees to Au(3+), which is supported by the observation that addition of molecular bromine also leads to similar results. A gratifying feature is that the Au(3+) ions could be subsequently reduced back to An nanoparticles.

Bacterial synthesis of copper/copper oxide nanoparticles - Hasan, Syed Saif; Singh, Sanjay; Parikh, Rasesh Y.; Dharne, Mahesh S.; Patole, Milind S.; Bhagavatula L. V. Prasad; Shouche, Yogesh S. (Journal of Nanoscience and Nanotechnology, 2008)
A bacterial mediated synthesis of copper/copper oxide nanoparticle composite is reported. A Gram-negative bacterium belonging to the genus Serratia was isolated from the midgut of Stibara sp., an insect of the Cerambycidae family of beetles found in the Northwestern Ghats of India. This is a unique bacterium that is quite specific for the synthesis of copper oxide nanoparticles as several other strains isolated from the same insect and common Indian mosquitoes did not result in nanoparticle formation. By following the reaction systematically, we could delineate that the nanoparticle formation occurs intracellularly. However, the process results in the killing of bacterial cells. Subsequently the nanoparticles leak out as the cell wall disintegrates. The nanoparticles formed are thoroughly characterized by UV-Vis, TEM, XRD, XPS and FTIR studies.
Keywords: bacterial synthesis; Nanoparticles; TEM; XPS; XRD

Bacterial synthesis of silicon/silica nanocomposites - Singh, Sanjay; Bhatta, Umananda M.; Satyam, P. V.; Dhawan, Alok; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
The synthesis of silicon/silica nanoparticle composites by the bacterium Actinobacter sp. is demonstrated. More specifically, the formation of silicon/silica nanocomposite is shown to occur when the bacterium is exposed to K(2)SiF(6) precursor under ambient conditions. Based on the earlier reports where this bacterium has been shown to synthesize iron oxide and iron sulfide nanoparticles, it is hypothesized that this bacterium secretes reductases and oxidising enzymes, which lead to the Si/SiO(2) nanocomposite synthesis. The particles obtained by bacterial synthesis were thoroughly characterized. The cytotoxicity studies revealed that the particles do not display any cytotoxicity to human skin cells. The synthesis of silica nanoparticles by bacteria in the present study demonstrates the versatility of the organism, and the formation of elemental silicon by this environmentally friendly process expands further the scope of microorganism based nanomaterial synthesis.

Bacteria-mediated precursor-dependent biosynthesis of superparamagnetic iron oxide and iron sulfide nanoparticles - Bharde, Atul A.; Parikh, Rasesh Y.; Baidakova, Marina; Jouen, Samuel; Hannoyer, Beatrice; Enoki, Toshiaki; Bhagavatula L. V. Prasad; Shouche, Yogesh S.; Ogale, Satishchandra B.; Sastry, Murali (Langmuir, 2008)
The bacterium Actinobacter sp. has been shown to be capable of extracellularly synthesizing iron based magnetic nanoparticles, namely maghemite (gamma-Fe2O3) and greigite (Fe3S4) Under ambient conditions depending on the nature of precursors used. More precisely, the bacterium synthesized maghemite when reacted with ferric chloride and iron sulfide when exposed to the aqueous solution of ferric chloride-ferrous sulfate. Challenging the bacterium with different metal ions resulted in induction of different proteins, which bring about the specific biochemical transformations in each case leading to the observed products. Maghemite and iron sulfide nanoparticles show superparamagnetic characteristics as expected. Compared to the earlier reports of magnetite and greigite synthesis by magnetotactic bacteria and iron reducing bacteria, which take place strictly under anaerobic conditions, the present procedure offers significant advancement since the reaction occurs under aerobic condition. Moreover, reaction end products can be tuned by the choice of precursors used.

Carbon nano horn and bovine serum albumin hierarchical composite: towards bio-friendly superhydrophobic protein film surfaces - Jadhav, Anil D.; Ogale, Satishchandra B.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
Highly hydrophilic glass substrates when coated with films of carbon nano horns dispersed in the ubiquitous protein bovine serum albumin display hydrophobic characteristics. Incidentally both the materials used to create the final hydrophobic surface are known to be highly bio-compatible. The features observed are accredited to the replication of the micro and nanoscale hierarchical structures of carbon nano horns in the final film composite.

C-glycosides of dodecanoic acid: new capping/reducing agents for glyconanoparticle synthesis - Ramana, C. V.; Durugkar, Kulbhushan A.; Puranik, Vedavati G.; Narute, Sachin B.; Bhagavatula L. V. Prasad (Tetrahedron Letters, 2008)
A concise synthesis of 12-C-glycosylated dodecanoic acids employing an olefin cross-metathesis reaction is developed. Examination of these acids as capping agents for the synthesis of metal nanoparticles reveals that they do not cap the Co-metal nanoparticles synthesized in aqueous phase, but that two of them can reduce and cap the Ag nanoparticles in water without any aggregation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: C-Glycosides; Cross metathesis; glyconanoparticles; Grubbs' catalyst; silver nanoparticles

Extracellular synthesis of crystalline silver nanoparticles and molecular evidence of silver resistance from morganella sp.: towards understanding biochemical synthesis mechanism - Parikh, Rasesh Y.; Singh, Sanjay; Bhagavatula L. V. Prasad; Patole, Milind S.; Sastry, Murali; Shouche, Yogesh S. (ChemBioChem, 2008)
There has been significant progress in the biological synthesis of nanomaterials. However, the molecular mechanism of synthesis of such bio-nanomaterials remains largely unknown. Here, we report the extracellular synthesis of crystalline silver nanoparticles (AgNPs) by using Morganella sp., and show molecular evidence I of silver resistance by elucidating the synthesis mechanism. The AgNPs were 20 +/- 5 nm in diameter and were highly stable at 1 room temperature. The kinetics of AgNPs formation was investigated. Detectable particles were formed after on hour of reaction, and their production remained exponential up to 18 h, and saturated at 24 h. Morganella sp. was found to be highly resistant to silver cations and was able to grow in the presence of more than 0.5 mm AgNO3. Three gene homologues viz. silE, silP and silS were identified in silver-resistant Morganella sp. The homologue of silE from Morganella sp. showed 99% nucleotide sequence similarity with the previously reported gene, silE, which encodes a periplasmic silver-binding protein. The homologues of silP and silS were also highly similar to previously reported sequences. Similar activity was totally absent in closely related Escherichia coli; this suggests that a unique mechanism of extracellular AgNPs synthesis is associated with silver-resistant Morganella sp. The molecular mechanism of silver resistance and its gene products might have a key role to play in the overall synthesis process of AgNPs by Morganella sp. An understanding of such biochemical mechanisms at the molecular level might help in developing an ecologically friendly and cost-effective protocol for microbial AgNPs synthesis.
Keywords: Biosynthesis; Morganella sp.; Nanoparticles; sil gene homologues; Silver

Gold nanoparticle superlattices - Bhagavatula L. V. Prasad; Sorensen, C. M.; Klabunde, Kenneth J. (Chemical Society Reviews, 2008)
Ordered metal nanoparticle assemblies-superlattices-have captivated and stirred the imagination of scientists and engineers alike and promise great prospect for future technologies. This potential though will greatly be determined by the understanding and control that can be exerted on the assembling processes. This tutorial review presents a brief account of the factors that govern the formation of superlattices and then presents several examples of gold nanoparticle superlattices that are distinguished by the size of participating particles, chain length/functional group of the capping agent, the substrates on which they form etc.

In situ synthesis of ligand reduced/capped silver nanoparticles and the effect of temperature and ligand structure on the size of silver nanoparticles - Kasture, M. B.; Patel, P.; Prabhune, Asmita; Ramana, C. V.; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Journal of Chemical Sciences, 2008)
We report in situ synthesis of silver nanoparticles using biosurfactants called sophorolipids as reducing and capping agents. We further study the effect of temperature and the structure of sophorolipid on the size of silver nanoparticles obtained. The silver nanoparticles were characterized by UV-visible, transmission electron microscope (TEM) and light scattering (DLS) analysis techniques.
Keywords: dynamic light scattering; Nucleation and growth; silver nanoparticles; Sophorolipid

Linear assembly of hexadecanethiol coated gold nanoparticles - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2008)
An interesting formation of linear assembly of hexadecanethiol coated gold nanoparticles is demonstrated. The nanoparticles used were synthesized in an organic medium and then were subjected to digestive ripening to finally yield monodisperse nanoparticles. A simple drop casting on TEM grid lead to the results observed. Based on the thermo gravimetric analysis, it is hypothesized that inclusion of the particles in Au(I)-thiolate template is mainly responsible for the formation of linear assembly. (c) 2008 Elsevier B.V. All rights reserved.

Natural gum reduced/stabilized gold nanoparticles for drug delivery formulations - Dhar, Sheetal; Reddy, E. Maheswara; Shiras, Anjali; Pokharkar, Varsha; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2008)
``Gellan Gum'', widely used in food and confectionary industry as a thickening and gelling agent, has been employed as a reducing and stabilizing agent for the synthesis of gold nanoparticles. These nanoparticles display greater stability to electrolyte addition and pH changes relative to the traditional citrate and borohydride reduced nanoparticles. Subsequently these have been used to load anthracycline ring antibiotic doxorubicin hydrochloride. The drug loaded on these nanoparticles showed enhanced cytotoxic effects on human glioma cell lines LN-18 and LN-229.
Keywords: Apoptosis; Cytotoxicity; drug delivery; Gold; Nanostructures; natural gums

Static and dynamic magnetic properties of Co nanoparticles - Srinath, S.; Poddar, P.; Sidhaye, Deepti S.; Bhagavatula L. V. Prasad; Gass, James; Srikanth, H. (Journal of Nanoscience and Nanotechnology, 2008)
Co nanoparticles have been synthesized using wet-chemical methods. As-synthesized particles show a sharp low temperature peak in zero-field cooled (ZFC) magnetization well below the blocking transition temperature and this feature is associated with surface spin disorder. We have investigated the dynamic magnetic properties of Co using ac susceptibility and resonant RF transverse susceptibility (TS). We also studied the memory and relaxation effects in these nanoparticle systems. From these measurements we show a typical blocking behavior of an assembly of superparamagnetic nanoparticles with a wide distribution of blocking temperatures. The transverse susceptibility measurements on these particles show the presence of anisotropy even above the blocking temperature. The role of surface anisotropy and the size distribution of the particles on the observed memory and magnetic relaxation effects are discussed.
Keywords: Ac Susceptibility; Co Nanoparticles; Magnetic relaxation; Transverse Susceptibility

Tunable surface modification of silica nanoparticles through `click' chemistry - Chandran, S. Prathap; Hotha, Srinivas; Bhagavatula L. V. Prasad (Current Science, 2008)
Tuning the surface functionality of silica nanoparticles through a `click' chemistry-based protocol is demonstrated. Pyrene, a fluorophore that displays excimer emission specifically at higher density/concentration is chosen for highlighting the fidelity of surface functionalization. The UV-visible absorbance of the pyrene chromophore capping the nanoparticle is used to determine the amount of pyrene units present on the surface of a silica nanoparticle.
Keywords: pyrene; silica nanoparticles; surface functionality; `Click' chemistry

Acute and subacute toxicity studies of chitosan reduced gold nanoparticles: a novel carrier for therapeutic agents - Pokharkar, Varsha; Dhar, Sheetal; Bhumkar, Devika; Mali, Vishal; Bodhankar, Subhash L.; Bhagavatula L. V. Prasad (Journal of Biomedical Nanotechnology, 2009)
The objective of the present study was to evaluate the oral toxicity of chitosan reduced gold nanoparticles so as to demonstrate its applicability for drug delivery application. Acute oral toxicity studies in female rats documented no deaths or treatment related complications. The LD(50) value of gold nanoparticles was found to be greater than 2000 mg/kg. In case of sub-acute oral toxicity studies, gold nanoparticles were administered orally to male and female rats for a period of 28-days. At the end of study blood samples were collected for haematology and biochemical analysis. For histopathological analysis, organs of animals were weighed and processed for examination. All animals survived the duration of the study, with no significant changes in clinical signs, body weight, food consumption, hematological parameters, organ weights and histopathological findings. These studies establish that chitosan reduced gold nanoparticles produced no treatment related toxicity in rats following oral administration, thus can be exploited for potential therapeutic applications.
Keywords: Acute Toxicity; Chitosan; gold nanoparticles; Sub-Acute Toxicity; Wistar Rats

Composites of plasma treated poly(etherimide) films with gold nanoparticles and lysine through layer by layer assembly: a ``friendly-rough'' surface for cell adhesion and proliferation for tissue engineering applications - D'Britto, Virginia; Tiwari, S.; Purohit, V.; Wadgaonkar, P. P.; Bhoraskar, S. V.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2009)
A composite film fabricated by plasma treated poly(etherimide) with subsequent deposition of gold nanoparticles and lysine using layer by layer assembly has been demonstrated to be good for cell attachment and proliferation making it an attractive strategy for tissue engineering applications. As compared to the other methods the decrease in contact angle obtained here does not depend much on the plasma treatment thus affecting the polymer structure minimally. A combination of surface roughness provided by the gold nanoparticles and the presence of amine groups of lysine is hypothesized to be the reason for the features observed.

Dendritic effect of ligand-coated nanoparticles: enhanced apoptotic activity of silica-berberine nanoconjugates - Halimani, Mahantappa; Chandran, S. Prathap; Kashyap, Sudhir; Jadhav, V. M.; Bhagavatula L. V. Prasad; Hotha, Srinivas; Maiti, Souvik (Langmuir, 2009)
We describe the synthesis and biological characterization of a novel prototype, namely, silica nanoconjugates bearing a covalently linked berberine, a plant alkaloid known to have antiproliferative activity. The effect of synthesized nanoconjugates on cell proliferation, the cell cycle profile, and apoptosis in the human cervical carcinoma cell line (HeLa), human hepatocellular liver carcinoma cell line (HepG2), and human embryonic kidney (HEK) 293T cell line has been studied and compared with the results obtained for free berberine. Our results show that all the nanoconjugates display higher antiproliferative activity than free berberine. The ability of these nanoconjugates to inhibit cellular proliferation is mediated by the cell cycle arrest at the G1 phase. Moreover, silica nanoconugates caused selective apoptotic arrest with a higher efficiency than free berberine followed by apoptotic cell death as shown by quantitative fluorescence-activated cell sorting analyses. Efficiency of the nanoconjugates increases upon an increase in the linker chain length, demonstrating the distinct role of the spacer chain that conjugates nanoparticles and ligands. The actual reason to show enhanced efficiency by the nanoconjugates has not been elucidated in the present study; however, we hypothesize that an increase in local concentration due to the confinement of a ligand on the nanosurface (''dendritic'' effect) might have led to the observed effect.

Direct method for the preparation of glycolipid-metal nanoparticle conjugates: sophorolipids as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles and their antibacterial activity - Singh, Sanjay; Patel, Pitamber; Jaiswal, Swarna; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2009)
The production of a new class of glycolipid-metal nanoparticle conjugates, namely, sophorolipid reduced/capped silver nanoparticles is demonstrated for the first time, by unveiling the reducing and capping abilities of sophorolipid derived from oleic acid. It is also demonstrated that the sophorolipid capped Ag nanoparticles are highly potent antibacterial agents, against both Gram-positive and Gram-negative bacteria. The utilization of sophorolipid brings out several advantages, such as eliminating the necessity for exogenous reducing agent and imparting better stability to the silver nanoparticles as compared to their oleic acid capped analogues. These sophorolipid capped silver nanoparticles can be obtained as a stable powder that can be re-dispersed in water as desired.

In situ synthesis of water dispersible bovine serum albumin capped gold and silver nanoparticles and their cytocompatibility studies - Murawala, Priyanka; Phadnis, S. M.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
A simple and convenient one step room temperature method is described for the synthesis of bovine serum albumin (BSA) capped gold and silver nanoparticles. BSA reduces silver ions to silver nanoparticles but does not directly reduce gold ions to gold nanoparticles at room temperature and varying pH conditions. However, when silver and gold ions are simultaneously added to BSA, silver ions get reduced to metallic silver first and these in turn reduce gold ions to gold nanoparticles through a galvanic exchange reaction. The so synthesized silver and gold nanoparticles are easily water dispersible and can withstand addition of salt even at high concentrations. It is shown that the capped protein retains its secondary structure and the helicity to a large extent on the nanoparticles surface and that the protein capping makes the nanoparticles cytocompatible. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag and Au nanoparticles; Bovine serum albumin; Cytocompatibility; Galvanic exchange reaction; Reductive synthesis

Intracellular biogenic silver nanoparticles for the generation of carbon supported antiviral and sustained bactericidal agents - Vijayakumar, P. S.; Bhagavatula L. V. Prasad (Langmuir, 2009)
Intracellular silver nanoparticles produced by exposing silver ions to the fungus Aspergillus ochraceus were heat-treated in nitrogen environment to yield silver nanoparticles embedded in carbonaceous supports. This carbonaceous matrix embedded silver nanoparticles showed antimicrobial properties against both bacteria (Gram-positive and Gram-negative) and virus (M 13 phage virus). The bactericidal effects were noticed even after washing and repealed exposure of these carbon supported silver nanoparticles to fresh bacterial Cultures, revealing their sustained activity.

Optical limiting properties of hydrophobic poly(etherimide) membranes embedded with isolated and aggregated gold nanostructures - D'Britto, Virginia; Sandeep, C. S. Suchand; Philip, R.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2009)
A simple method to incorporate spherical or aggregated nanostructures of gold into hydrophobic poly(etherimide) membranes is demonstrated and their comparative nonlinear optical properties are investigated. When excited at 532 nm using laser pulses of 7 ns duration, a reduced transmission behaviour in both the cases, viz., polymers embedded with isolated nanoparticles and their aggregates is observed. This fits to a three-photon type nonlinear absorption process and is attributed to excited state absorption occurring in the nanostructures. Interestingly, the nonlinearity is more prominent in the aggregated nanostructures compared to the spherical nanostructures. These materials are potential candidates for optical limiting applications. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: gold nanoparticles; Nanoparticle aggregation; Nonlinear optical properties; Optical limiting; Phase transfer; Polymer nanocomposites

Preparation of nearly monodisperse nickel nanoparticles by a facile solution based methodology and their ordered assemblies - Sidhaye, Deepti S.; Bala, Tanushree; Srinath, S.; Srikanth, H.; Poddar, Pankaj; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2009)
Nickel nanoparticles have been synthesized by a simple wet chemical reduction technique in the presence of a surfactant sodium dodecyl sulfate (SDS) and a capping agent oleic acid. Varying the concentration of the surfactant and the capping agent has been found to critically govern the nature of the nanoparticles prepared. It is observed that at an optimum concentration of SDS and oleic acid, nearly monodisperse Ni nanoparticles are obtained that form highly ordered hexagonally close-packed structures on electron microscopy grids by a simple drop coating procedure. It is also shown that the presence of oleic acid is necessary for the stability of the Ni nanoparticles synthesized. Structural and magnetic characterizations of the nanoparticles are also presented.

Synthesis of Ag-Pt alloy nanoparticles in aqueous bovine serum albumin foam and their cytocompatibility against human gingival fibroblasts - Singh, A. V.; Patil, R.; Kasture, M. B.; Gade, Wasudeo N.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
Foams of bovine serum albumin (BSA) have been utilized for synthesizing in situ protein capped Ag-Pt alloy nanoparticles. The in vitro cytotoxicity and the rate of proliferation of human gingival fibroblasts (HGFs) in presence of the above synthesized alloy nanoparticles is investigated. Expression profile of protein involved in detoxification, i.e. metallotheonein (MT) were assayed by ELISA and expression of mRNA transcripts by reverse transcription polymerase chain reaction (RT-PCR). Cytotoxicity results suggested that protein capped nano-alloys might be promising candidates for implants and prosthetic material. RT-PCR and ELISA confirmed the expression of MT. in cells treated with the alloy nanoparticles. Morphology variation studied by SEM also confirms that cells treated with alloy nanoparticles present an intact morphology. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alloy nanoparticles; Biocompatibility; ELISA; Human gingival fibroblasts; mRNA; Protein foams

Synthesis of hydroxy-functional PMMA macromonomers by anionic polymerization - Dhara, Mahua Ganguly; Sivaram, Swaminathan; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2009)
Living anionic polymerization has been utilized to synthesize hydroxy end-functionalized PMMA macromonomers with styryl or allyl functionalities as the polymerizable end-groups. Protected hydroxy-functionalized alkyl lithium initiators have been used to initiate anionic polymerization of MMA. Subsequently the living chains with protected hydroxyl function have been terminated using 4-vinylbenzyl chloride (4-VBC) or allyl methacrylate (ALMA) to form -hydroxy–styryl and -hydroxy–allyl PMMA, respectively. These protected hydroxy-functionalized PMMA macromonomers have been characterized by GPC and 1H-NMR. Termination using 4-VBC led to 50% functionalization, whereas that using allyl methacrylate led to 100% functionalization of the hydroxy-PMMA.
Keywords: Anionic polymerization; functionalized initiator; Macromonomer

Bacterial synthesis of phtocatalytically active and biocompatible TiO2 and ZnO nanoparticles - Singh, Sanjay; Britto, Virginia D.; Bharde, Atul A.; Sastry, Murali; Dhawan, Alok; Bhagavatula L. V. Prasad (International Journal of Green Nanotechnology: Physics and Chemistry, 2010)
TiO2 and ZnO nanoparticles are well known for their photocatalytic and ultraviolet (UV)-absorbent properties and have successfully entered into the market as consumer products. Large volume production of these nanoparticles by industries require environmentally friendly processes of synthesis. In this article, we show that when challenged with an appropriate precursor, the bacterium Actinobacter spp. can lead to the extracellular synthesis of ZnO and TiO2 nanoparticles. The biological way of synthesizing these materials probably leads to the in situ doping of elements like C, F, and N into their crystal lattices, which is evidenced by a red shift in the absorption edge. Because the doping is expected to affect the photocatalytic activity of these materials under different light conditions, such investigations have also been undertaken here. Further, the biocompatibility of these nanomaterials (cytotoxicity and genotoxicity) has also been investigated in detail.
Keywords: Biosynthesis; genotoxicity; Nanoparticles; Nanotoxicity; Photocatalysis

Citrate-capped quantum dots of CdSe for the selective photometric detection of silver ions in aqueous solutions - Ingole, Pravin P.; Rajiv M. Abhyankar; Bhagavatula L. V. Prasad; Haram, Santosh K. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A simple strategy for the synthesis of water soluble, luminescent, citrate-capped CdSe quantum dots (Q-CdSe) and their applications to selective detection of silver ions are described. The steady state photoluminescence (PL) spectra show single, narrow emission band at ca. 554 nm without any contribution from the trap states. The effect of various ions including physiologically important metal ions (viz. K(+), Ca(2+), Fe(3+), Zn(2+), Mg(2+), Mn(2+), Cu(2+), Ag(+), Pb(2+) and Cd(2+)), on the PL intensity of citrate-capped Q-CdSe has been studied. Among these, selective luminescence quenching with Ag(+) ion was found to be predominant. Under the optimum conditions, the response was linear between 1.7 and 18 mu M. The quenching constant K(SV) was found to be ca. 3.4 x 10(5) M(-1). The mechanism of photoluminescence quenching of Q-CdSe by metal ions (Ag(+)) is also discussed. Based on these studies, the potential use of Q-CdSe as a luminescent probe for the selective detection of silver ion has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag(+) ions; Luminescence quenching; Luminescent probe; Q-CdSe; Tri-sodium citrate

Clicking molecular hooks on silica nanoparticles to immobilize catalytically important metal complexes: the case of gold catalyst immobilization - Ganai, Anal Kumar; Bhardwaj, Rima; Hotha, Srinivas; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
Gold mediated reactions have emerged as one of the best choices for affecting a variety of chemical transformations with a wide range of functional group tolerance. Application of such transformations to industrial processes necessitates immobilization of the Au ions into a matrix for easy separation of the catalyst after reaction. We report the synthesis and characterization of silica nanoparticles in which Au(III) has been immobilized through a 1,2,3-triazole linkage using an alkynalated picolinic acid exploiting ``click chemistry''. The Au( III) immobilized silica nanoparticle has been thoroughly characterized using FT-IR, C-13 CP MAS NMR and XPS. The utility of these particles as an easily separable catalyst for the Hashmi phenol synthesis is also reported.

Continuous flow synthesis of functionalized silver nanoparticles using bifunctional biosurfactants - Kumar, D. V. Ravi; Kasture, Manasi; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Green Chemistry, 2010)
Silver nanoparticles were synthesized by continuous flow methods using biosurfactants, namely, oleic acid sophorolipid (OASL) and stearic acid sophorolipid (SASL). Both the sophorolipids can act as reducing and capping agents. The effect of temperature on the completion of nanoparticle formation and the particle growth dynamics (size) were studied in batch mode. While the completion of the reaction using oleic acid sophorolipid needed 20 min, only 5 min were required with the stearic acid sophorolipid as capping and reducing agent. Hence all the continuous flow experiments were carried out using the stearic acid sophorolipid. The continuous flow synthesis of silver nanoparticles was carried out in a stainless steel helical coil and also in a spiral polymeric minichannel reactor. The DLS results show that higher flow rate leads to the formation of bigger and polydisperse particles because of incomplete reactions. Higher residence time allowed the completion of reaction leading to spherical, small and monodisperse particles.

Cytotoxic and genotoxic assessment of glycolipid-reduced and -capped gold and silver nanoparticles - Singh, Sanjay; D'Britto, Virginia; Prabhune, Asmita; Ramana, C. V.; Dhawan, Alok; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
A systematic cytotoxic and genotoxic evaluation of glycolipid-conjugated silver and gold nanoparticles is carried out. These glycolipid nanoparticle conjugates are obtained by exploiting the reductive capability of a class of glycolipids called sophorolipids that play the role of capping agent as well. Further, when tested for their cytotoxicity and genotoxicity on HepG2 cells, these nanoparticles are found to be cytocompatible up to 100 mu M metal concentrations. Of the two metallic systems investigated, gold nanoparticles are found to be more cytocompatible than the same concentrations of silver nanoparticles. Similarly, it is also demonstrated that at 100 mu M, silver nanoparticles cause more DNA damage compared to gold nanoparticles of similar concentrations.

Enhancement of anisotropic conductivity, elastic, and dielectric constants in a liquid crystal-gold nanorod system - Sridevi, S.; Prasad, S. Krishna; Nair, Geetha G.; D'Britto, Virginia; Bhagavatula L. V. Prasad (Applied Physics Letters, 2010)
We report electrical conductivity (sigma), dielectric constant (epsilon) and the elastic constant measurements in a nematic liquid crystal (LC) doped with small concentrations of gold nanorods. This LC-nanoparticle complex, shows not only orders of magnitude higher sigma, but also stabilizes its anisotropy. The epsilon data suggests an increased ordering in the nematic phase, and an improved antiparallel correlation of the molecules in the isotropic phase. Surprisingly, an anisotropic enhancement of the Frank elasticity is also seen. We suggest a possible electro/magnetomechanical conductivity switch and also provide explanations based on the aspect ratio of the nanoparticles vis-a-vis the LC molecules. (c) 2010 American Institute of Physics. [doi:10.1063/1.3499744]

Field dependence of the magnetocaloric effect in core-shell nanoparticles - Franco, V.; Conde, A.; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Poddar, P.; Srinath, S.; Phan, M. H.; Srikanth, H. (Journal of Applied Physics, 2010)
The field dependence of the magnetic entropy change peak at the low temperature surface spin freezing transition in chemically synthesized, monodispersed Co, Co-Ag, and Ni-Ag core-shell nanoparticles is studied, with the aim of gaining insight into the critical exponents of this transition. It is evidenced that although the magnitude of the peak entropy change and position of the peak can be tuned by changing the composition and nature (metallic or organic) of the shell and surfactant layers, the characteristics of the spin freezing transition are not altered. The field dependence of the refrigerant capacity also confirms this finding. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3335514]

Halide ion controlled shape dependent gold nanoparticle synthesis with tryptophan as reducing agent: enhanced fluorescent properties and white light emission - Kasture, Manasi; Sastry, Murali; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2010)
We report the synthesis of Au nanoparticles in presence of two surfactants cetyltrimethyl ammonium chloride (CTAC) and cetyltrimethyl ammonium bromide (CTAB) by reducing Au(3+) ions with tryptophan. Interestingly, triangular shaped particles were seen to form in presence of CTAB, while spherical nanoparticles resulted with CTAC. The highlight of this result is the white light emission from the Au triangles obtained when CTAB is used. These results are supported by lifetime measurements and fluorescence. (C) 2009 Elsevier B. V. All rights reserved.

Investigation of magnetic anisotropy in Co nanoparticles using ferromagnetic resonance technique - Sendilkumar, A.; Kasture, Manasi; Patel, Pitamber; Ramana, Chepuri V.; Bhagavatula L. V. Prasad; Srinath, S. (Journal of Physics: Conference Series, 2010)
Using ferromagnetic resonance (FMR) technique, we have investigated the temperature dependence and angular dependence of line width and resonance magnetic field of Co nanoparticles capped with novel alkane carboxylic acids of varying chain lengths. The magnetic properties such as blocking temperature and anisotropy sensitively depend on the chain length as evidenced by the temperature dependence of line width. These results indicate that the magnetic properties of these samples are critically governed by the interparticle interactions which are decided by the chain length. The presence of anisotropy even up to very high temperature above the blocking temperature observed in these studies confirms the presence of inter-particle magnetic interactions as well as intra-particle exchange interaction between the core and shell regions as evidenced by our earlier ac susceptibility and transverse susceptibility measurements on similar system.

Melting characteristics of superlattices of alkanethiol-capped gold nanoparticles: the ``excluded'' story of excess thiol - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (Chemistry of Materials, 2010)
Melting characteristics of gold nanoparticle superlattices obtained from nanoparticles capped by alkanethiols of different chain lengths (octane, dodecane and hexadecane) have been investigated. The alkanethrol capped nanoparticles were synthesized by the well-established digestive ripening method It is observed that as the chain length Of the thiol increases, the propensity to form superlattices decreases and the melting of the superlattice is observed at lower temperature However, the Formation of the 3D superlattice is critically dependent on the presence of ``excess'' thiol as determined from thermogravimetric and transmission electron microscope analysis. In the absence of ``excess'' thiol, only 2D hexagonally close-packed arrangements were seen

Nanogold-Loaded sharp-edged carbon bullets as plant-gene carriers - Vijayakumar, Periyasamy S.; Othalathara U. Abhilash; Khan, Bashir Mohammad; Bhagavatula L. V. Prasad (Advanced Functional Materials, 2010)
The higher DNA delivery efficiency into plants by gold nanoparticles embedded in sharp carbonaceous carriers is demonstrated. These nanogold-embedded carbon matrices are prepared by heat treatment of biogenic intracellular gold nanoparticles. The DNA-delivery efficiency is tested on a model plant, Nicotiana tabacum, and is further extended to the monocot, Oryza sativa, and a hard dicot tree species, Leucaena leucocephala. These materials reveal good dispersion of the transport material, producing a greater number of GUS foci per unit area. The added advantages of the composite carrier are the lower plasmid and gold requirements. Plant-cell damage with the carbon-supported particles is very minimal and can be, gauged from the increased plant regeneration and transformation efficiency compared with that of the commercial micrometer-sized gold particles. This is ascribed to the sharp edges that the carbon supports possess, which lead to better piercing capabilities with minimum damage.

Synthesis and characterization of poly-L-lysine-grafted silica nanoparticles synthesized via NCA polymerization and click chemistry - Kar, Mrityunjov; Vijayakumar, P. S.; Bhagavatula L. V. Prasad; Sen Gupta, Sayam (Langmuir, 2010)
Polypeptide polymer-grafted silica nanoparticles are of considerable interest because the ordered secondary structure of the polypeptide grafts imparts novel functional properties onto the nanoparticle composite. The synthesis of poly-L-lysine-grafted nanoparticles would be of particular interest because the high density of cationic charges on the surface could lead to many applications such as gene delivery and antimicrobial agents. In this work, we have developed a ``grafting-to'' approach using a combination of NCA polymerization and ``click chemistry'' to synthesize poly-L-lysine-grafted silica nanoparticles with a high graft density of 1 chain/nm(2). The covalent attachment of poly-L-lysine to silica nanoparticles (PLL-silica) was confirmed using a variety of techniques such as C-13 CP MAS NMR, TGA, and IR. This methodology was then extended to graft poly-L-lysine-b-poly-L-leucine copolymer (PLL-b-PLLeu-silica) and poly-L-benzylglutamate (PLUG silica) onto silica nanoparticles. All of these polypeptide-grafted nanoparticles show interesting aggregation properties in solution. The efficacy of PLL-silica and PLL-h-PLLeu-silica as antimicrobial agents was tested on both gram-negative B. cull and grain-positive Bacillus subtilis.

Vice to virtue: intracellular biogenic nanoparticles for the generation of carbon supported catalysts - Vijayakumar, P. S.; Selvakumar, S.; Gholap, Ramkrishna S.; Singh, A. P.; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2010)
Intracellular biogenic nanoparticles are considered disadvantageous as the separation of the nanoparticles from the biomass becomes intricate. However realizing the importance of carbon supported catalyst for many important organic reactions we envisaged these nanoparticles as a source for carbon supported catalyst. Herein we demonstrate the heat treatment of intracellular biogenic nanoparticles under inert atmosphere as an efficient method for the preparation of carbon supported metal oxide catalysts. Aspergillus ochraceus, a fungus isolated from foundries, on incubation with K(2)TiF(6) led to the synthesis of intracellular titanium oxide nanoparticles. The nanoparticles embedded biomass upon heat treatment at 600 degrees C in a nitrogen environment gave titanium oxide nanoparticles implanted in a carbonaceous matrix. The material thus formed was characterized using FTIR spectroscopy, Raman spectroscopy, HRTEM and X-ray diffraction. Appreciable benzaldehyde selectivity was observed when styrene oxidation was carried out over such immobilized catalysts. The conversion rate was determined to be 76% and the benzaldehyde selectivity was greater than 80%.
Keywords: Benzaldehyde Selectivity; Biosynthesis; Carbon Supported Titania; Nanoparticles; Styrene Oxidation

Biocompatible gellan gum-reduced gold nanoparticles: cellular uptake and subacute oral toxicity studies - Dhar, Sheetal; Mali, Vishal; Bodhankar, Subhash L.; Shiras, Anjali; Bhagavatula L. V. Prasad; Pokharkar, Varsha (Journal of Applied Toxicology, 2011)
Currently gold nanoparticles are being explored for drug delivery and other biomedical applications; therefore it is necessary to study the fate of such nanoparticles inside the body. The objective of the present study was to investigate the cellular uptake and toxicity of the gold nanoparticles synthesized using a microbial polysaccharide, gellan gum, as a capping and reducing agent. The cellular uptake of gold nanoparticles was studied on mouse embryonic fibroblast cells, NIH3T3 and human glioma cell line, LN-229. The cellular uptake study indicated that the gellan gum-reduced gold nanoparticles were located in cancer cells (LN-229) while no uptake was observed in normal mouse embryonic fibroblast cells (NIH3T3). The toxicity of the gold nanoparticles was evaluated by carrying out subacute 28 day oral toxicity studies in rats. Subacute administration of gum-reduced gold nanoparticles to the rats did not show any hematological or biochemical abnormalities. The weight and normal architecture of various organs did not change compared with control. The current findings, while establishing the specific uptake of nanoparticles into cancerous cells, also demonstrates that the gellan gum-reduced gold nanoparticles are devoid of toxicity in animals following oral administration. Copyright (c) 2010 John Wiley & Sons, Ltd.
Keywords: cell lines; cellular uptake; Gellan gum; gold nanoparticles; subacute toxicity

Cytotoxicity of sophorolipid-gellan gum-gold nanoparticle conjugates and their doxorubicin loaded derivatives towards human glioma and human glioma stem cell lines - Dhar, Sheetal; Reddy, E. Maheswara; Prabhune, Asmita; Pokharkar, Varsha; Shiras, Anjali; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Biocompatible gold nanoparticles were synthesized by using a naturally occurring gum-Gellan Gum-as a capping and reducing agent. These were further conjugated with sophorolipids which again were accessed through a biochemical transformation of a fatty acid. The cellular uptake of sophorolipid-conjugated gellan gum reduced gold nanoparticles and their cytotoxicity on human glioma cell line LN-229 and human glioma stem cell line HNGC-2 were investigated. Quite surprisingly even the simple sophorolipid-conjugated gellan gum reduced/capped gold nanoparticles showed greater efficacy in killing the glioma cell lines and, gratifyingly, the glioma stem cell lines also. The cytotoxic effects became more prominent once the anti cancer drug doxorubicin hydrochloride was also conjugated to these gold nanoparticles.

Many manifestations of digestive ripening: monodispersity, superlattices and nanomachining - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2011)
Digestive ripening has now been established as a very convenient route to obtain monodisperse nanoparticles from polydisperse ones by refluxing the latter in the presence of an excess ligand. Many ligands including long chain thiols, amines, or phosphines have been shown to be effective digestive ripening agents. It is hypothesized that the surface active groups of such digestive ripening agents bind and remove reactive surface atoms/clusters from big nanoparticles and redeposit them on smaller nanoparticles. In this way, large particles become smaller, while small particles become larger, and eventually, an equilibrium size is obtained that is specific to each of the digestive ripening agents used. Herein, the digestive ripening procedure is reviewed, discussed and its utility spanning the preparation of monodispersed metal nanoparticles, alloy nanoparticles, superlattice structures and the most interesting nano-machining (wherein the monodisperse particles can be reverted back to the polydisperse system) is demonstrated.

Silver nanoparticle studded porous polyethylene scaffolds: bacteria struggle to grow on them while mammalian cells thrive - D'Britto, Virginia; Kapse, Harsha; Babrekar, Harshada A.; Prabhune, Asmita; Bhoraskar, S. V.; Premnath, V.; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Silver nanoparticle studded scaffolds were prepared by exploiting the Ag+ ion reducing activity of sophorolipids-a class of `glycolipids' that cap the ensuing nanoparticles as well. To achieve this, the porous polyethylene scaffolds are subjected to N-2+H-2 plasma treatment, in the first step. Subsequently the sophorolipids are covalently attached to the amine groups on the polymer surface through simple amide chemistry to yield sophorolipid grafted polymer scaffolds. These are then exposed to Ag+ ions under appropriate conditions leading to the formation of silver nanoparticles immobilized on the polymer scaffolds. It has been found that while bacteria do not survive on these silver studded scaffolds, CHO-K1 cells thrive on them making them good candidates for tissue engineering and bio-implant applications.

Effect of digestive ripening agent on nanoparticle size in the digestive ripening process - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2012)
Digestive ripening is an efficient method that leads to monodispersed nanoparticles from polydispersed ones. A systematic investigation of digestive ripening with different agents viz. dodecanethiol and dodecylamine on different metallic systems is presented. It is shown that both the metallic system involved and the digestive ripening agent have influences on the final size distribution. Further, it is demonstrated that the interaction strength between the different metals and the digestive ripening agents based on Hard Soft Acid Base principles could be invoked to explain the variation in nanoparticle size. (C) 2012 Elsevier B.V. All rights reserved.

Foam based synthesis of metal carbonates: establishing the role of spatial confinement for obtaining interesting morphologies - Bala, Tanushree; Sanyal, Ambarish; Pant, Jayashree; Bhagavatula L. V. Prasad (Journal of Computational and Theoretical Nanoscience, 2012)
The crystallization of different carbonates namely lead carbonate, cadmium carbonate and strontium carbonate in aqueous foam stabilized by the surfactant sodium dodecyl sulphate (SDS) by a method of cation entrapment is described. Reaction of ammonium carbonate with the respective cations electrostatically entrapped in the foam results in the formation of minerals, possibly in the Plateau border and Plateau junction regions of the foam. The unusual morphology of the crystals obtained from foam based synthetic method as compared to the crystals prepared in aqueous solution shows the utility of the template for the growth of crystals with an unusual morphology due to constrained environment. The materials are well characterized using TEM, SEM, EDAX and FTIR techniques. The large interfacial area of the liquid lamellae in the foam provides a striking possibility for the large-scale synthesis for not only minerals but also other nanoscale materials.

Gellan gum capped silver nanoparticle dispersions and hydrogels: cytotoxicity and in vitro diffusion studies - Dhar, Sheetal; Murawala, Priyanka; Shiras, A.; Pokharkar, V.; Bhagavatula L. V. Prasad (Nanoscale, 2012)
The preparation of highly stable water dispersions of silver nanoparticles using the naturally available gellan gum as a reducing and capping agent is reported. Further, exploiting the gel formation characteristic of gellan gum silver nanoparticle incorporated gels have also been prepared. The optical properties, morphology, zeta potential and long-term stability of the synthesized silver nanoparticles were investigated. The superior stability of the gellan gum-silver nanoparticle dispersions against pH variation and electrolyte addition is revealed. Finally, we studied the cytotoxicity of AgNP dispersions in mouse embryonic fibroblast cells (NIH3T3) and also evaluated the in vitro diffusion of AgNP dispersions/gels across rat skin.

Gold nanoparticle embedded hydrogel matrices as catalysts: better dispersibility of nanoparticles in the gel matrix upon addition of N-bromosuccinimide leading to increased catalytic efficiency - Ramtenki, Vilas; Anumon, V. D.; Badiger, Manohar V.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2012)
A simple and convenient method for generating and immobilizing gold NPs into polyethylene glycol-polyurethane (PEGPU) matrices is presented. The gold NP immobilized PEGPU (Au NP-PEGPU) hydrogel matrices are easy to handle and can be used as catalysts. The efficiency, reusability and durability of the Au NP-PEGPU catalyst matrices were investigated using the reduction of 4-nitroaniline (4NA) to p-phenylenediamine (p-PDA) by sodium borohydride in the presence of the catalyst as a test reaction. The Au NPs in the PEGPU matrix got aggregated after 3 cycles of catalysis but dispersion could be regenerated by the addition of N-bromosuccinimide (NBS). After this regeneration process the Au NPs-PEGPU matrix showed excellent efficiency without any aggregation, leaching or degradation. The reusability of the catalyst for 28 cycles yielding a total turnover number of 3220 and turn over frequency of 0.152 s(-1) is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: catalysis; hydrogels; Immobilization; Nanoparticles; Turn over numbers

Segmented flow synthesis of Ag nanoparticles in spiral microreactor: role of continuous and disperzsed phase - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, Amol A. (Chemical Engineering Journal, 2012)
This work focuses on understanding the effect of segmented flow on the nanoparticle size distribution in a unidirectionally expanding spiral microreactor, where secondary flows are prevalent in the absence of segmentation. Stearic acid sophorolipid reduced/capped Ag NPs were synthesized in the aqueous phase and air or kerosene was used as inert phases for creating the gas-liquid and liquid-liquid segmented flow, respectively. While, in one case the reactant phase is in the form of dispersed phase slugs, in the other case it is in the form of continuous phase, each exhibiting a different behavior. The slug sizes and the slip velocity, both of which govern the nature of internal mixing in the reactant phase slug controlled the nanoparticle size distribution. This observation was consistent for both, gas-liquid and liquid-liquid segmented flows. The micromixer having smaller orifice diameter yielded smaller slugs and also a narrow particle size distribution. In general, the particle sizes were much smaller for gas-liquid flow rather than for liquid-liquid flow. Because of the unidirectionally expanding spiral geometry of the channel, at any given condition, unsteady behavior of slugs due to continuously varying radius of curvature results in variation in the slip velocity along the length of microchannel. This effect was seen to further narrow the particle size distribution than alone by the segmented flow. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ag nanoparticles; Segmented flow synthesis; Sophorolipid; Spiral microreactor

Development of a multifunctional catalyst for a ``relay'' reaction - Ganai, Anal Kumar; Shinde, Pravin; Dhar, Basab B.; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (RSC Advances, 2013)
In the area of catalysis, nanoparticles and enzymes are two of the most important systems. By amalgamating the two, we present here proof of the concept that it is possible to prepare a multifunctional catalyst that can carry out a ``relay'' reaction. The catalyst consists of a surface bound enzyme on a metal(core)-silica(shell) nanoparticle architecture. Here the enzyme catalyzes the 1st reaction and the metal nanoparticles act as a catalyst for the 2nd reaction of the product from the 1st reaction. In particular, we have studied the catalytic activity of glucosidase grafted Au@mSiO(2) on 4-nitrophenyl-beta-glucopyranoside, where glucosidase will catalyse the 1st step to generate 4-nitrophenol, which acts as a substrate for the next reduction step which is catalysed by the Au nanoparticles present inside the mesoporous silica shell.

Exclusion from hexagonal mesophase surfactant domains drives end-to-end enchainment of rod-like particles - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen, Debasis; Bhagavatula L. V. Prasad; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2013)
Anisotropic rod-like particles assemble end-to-end when the surfactant/water matrix in which they are dispersed is cooled from the isotropic to the lyotropic hexagonal phase. We demonstrate the formation of such end-to-end assemblies for gold nanorods, which are tens of nanometers in size, as well as for micrometer-sized ellipsoidal polystyrene particles. In both cases, the particles are well-dispersed in the low-viscosity surfactant/water phase above the isotropic-H-1 transition temperature. On cooling into the H-1 phase, mesophase domains form and the particles are expelled to the isotropic phase. As the H-1 domains grow and finally impinge, the particles are localized at the domain boundaries where they reorient and assemble end-to-end. Remarkably, we observe the formation of end-to-end assemblies of gold nanorods even for volume fractions as low as 2 x 10(-6) in the initially dispersed state. The extent of particle ``enchainment'' increases with the particle concentration and with the aspect ratio of the particles.

Fine control of nanoparticle sizes and size distributions: temperature and ligand effects on the digestive ripening process - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Nanoscale, 2013)
It is demonstrated that a fine control over the size and size distribution of nanoparticles could be achieved using digestive ripening at different temperatures. Such variations in size and size distributions hugely influence the self-assembled processes in nanoparticles, and result in superlattice structures that are controlled by subtle interplay between ligand orientational entropy and their interdigitation and the van der Waals attraction between the metal cores.

Impinging jet micromixer for flow synthesis of nanocrystalline MgO: role of mixing/impingement zone - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Industrial & Engineering Chemistry Research, 2013)
Continuous flow synthesis of nanomaterials via sol-gel process using microreactors has not received much attention. For the synthesis of gels where the reaction time is of the order of few seconds to few tens of seconds, microchannel reactors are an excellent processing option. However since a `gel' does not `flow' easily, making it in a microchannel usually clogs the microchannel. We envisaged that by using an impinging jet micromixer, where the two reactants impinge and collide to form a mixing zone outside the micromixer, this problem could be circumvented. Here we report a successful implementation of continuous flow synthesis of metal oxides formed by the rapid sol-gel process taking the nanocrystalline MgO (NC-MgO) as a specific example. Furthermore, we clearly demonstrate that the nature of the mixing zone formed by the impinging jets governs the surface area of the product. Specific flow rate and impingement angle are identified that yield high surface area materials.

Influence of the sophorolipid molecular geometry on their self-assembled structures - Dhasaiyan, Prabhu; Banerjee, Agnimitra; Visaveliya, Nikunjkumar; Bhagavatula L. V. Prasad (Chemistry-an Asian Journal, 2013)
Keywords: bolaamphiphiles; helical structures; p-p stacking; Self-assembly; sophorolipids

Surfactant-free synthesis of anisotropic gold nanostructures: can dicarboxylic acids alone act as shape directing agents? - Kumar, D. V. Ravi; Kumavat, S. R.; Chamundeswari, V. N.; Patra, Partha Pratim; Kulkarni, A. A.; Bhagavatula L. V. Prasad (RSC Advances, 2013)
The present study describes the synthesis of gold nanostructures using different dicarboxylic (viz. oxalic, malonic, succinic, glutaric and adipic) acids as reducing agents in the absence of any other additives or surfactants. Various anisotropic structures such as kites, tadpoles, triangular/hexagonal plates, and twinned particles were seen to evolve depending on the molar ratio of dicarboxylic acid to HAuCl4 used. It was also demonstrated that gold nanostructure formation is hampered as the chain length/distance between two carboxylic acid groups increases. Among the various structures obtained the kite like structures displayed the largest surface enhanced Raman enhancement factors.

Synthesis of Ag-glyconanoparticles using C-glycosides, their lectin binding studies and antibacterial activity - Ramtenki, Vilas; Raju, D.; Mehta, Urmil J.; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2013)
Two 12-C-glycosyl dodecanoic acids, namely, 1-(alpha-D-mannopyranosyl)-12-dodecanoic acid and 1-(alpha-D-glucopyranosyl)-12-dodecanoic acid were synthesized. Their ability to act as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles is displayed. These Ag C-glycosyl nanoparticles were later utilized to investigate the carbohydrate-lectin interactions. Furthermore, the specificity of mannoside binding to the surface of the Gram negative bacterium Escherichia coli has been utilized to demonstrate the enhanced antibacterial activity of Ag-C-mannosyl nanoparticles towards this bacterium as compared to Ag-C-glycosyl nanoparticles.

Synthesis of triangular gold nanoplates: role of bromide ion and temperature - Kumar, D. V. Ravi; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2013)
Synthesis of noble metal triangular nanoplates is a kinetically controlled process in which temperature and packing defects play a major role. Nucleation and growth process of kinetically controlled reaction can be greatly influenced by temperature affecting the yield and edge length of the triangles. Through a conventional batch mode process, here we study the effect of temperature on nucleation and growth of gold triangular nanoplates and obtain some insight of the temperature effects on the final yield and edge length of triangles. The role of Br- ions in the synthesis of triangular nanoplates is studied by varying the amount of CAB and by replacing the CTAB with HBr. The results show that, while CTAB controls the edge length and yield of triangles, its use is not mandatory to attain plate like morphology. Finally we show that, while the initial temperature of the reaction mixture governs the nucleation rate and the rate of temperature rise governs the growth rate of particles, they along with the concentration of Br- ions control the edge length and yield. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Halide ion effect; heat transfer; Kinetically controlled; Nature of gold precursor complex; Nucleation and growth; Optical properties

Access to harmonine, a chemical weapon of ladybird beetles - Philkhana, Satish Chandra; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Reddy, D. Srinivasa (RSC Advances, 2014)
The synthesis of harmonine, a defense alkaloid from the harlequin ladybird is reported by three different routes. The preparation of several new analogs with the same molecular weight and the decoration of gold nanoparticles with harmonines are also part of the present communication.

Dilution does the trick: role of mixed solvent evaporation in controlling nanoparticle self-assembly - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
An easy and convenient way to prepare superlattices of amine capped gold nanoparticles is presented. It is clearly established that solvent evaporation significantly influences the nature of resulting superlattices and critically governs whether monolayer or multilayer superlattices are formed. More specifically, it is demonstrated that dilution of the nanoparticle dispersion with a similar solvent (but with different vapour pressure) is an expedient handle to control the nature of self-assembly. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Evaporation rate; gold nanoparticles; Nucleation; Self-assembly

In situ synthesized BSA capped gold nanoparticles: effective carrier of anticancer drug methotrexate to MCF-7 breast cancer cells - Murawala, Priyanka; Tirmale, Amruta; Shiras, Anjali; Bhagavatula L. V. Prasad (Materials Science & Engineering C-Materials For Biological Applications, 2014)
The proficiency of MTX loaded BSA capped gold nanoparticles (Au-BSA-MTX) in inhibiting the proliferation of breast cancer cells MCF-7 as compared to the free drug Methotrexate (MTX) is demonstrated based on MTT and Ki-67 proliferation assays. In addition, DNA ladder gel electrophoresis studies, flow cytometry and TUNEL assay confirmed the induction of apoptosis by MTX and Au-BSA-MTX in MCF-7 cells. Notably, Au-BSA-MTX: was found to have higher cytotoxicity on MCF-7 cells compared with an equivalent dose of free MTX. The enhanced activity is attributed to the preferential uptake of Au-BSA-MTX particles by MCF-7 cells due to the presence of BSA that acts as a source of nutrient and energy to the rapidly proliferating MCF-7 cells. Moreover, the targeting ability of the drug MTX to the over expressed folate receptors on MCF-7 cells also contributes to the enhanced uptake and activity. Taken together, these results unveil that Au-BSA-MTX could be more effective than free drug for cancer treatment. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Apoptosis; Bovine serum albumin; Cancer therapy; Cytotoxicity; Dual active agents; gold nanoparticles

Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic

Microfluidic platform for continuous flow synthesis of triangular gold nanoplates - Kumar, D. V. Ravi; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
A microfluidic platform for the continuous flow synthesis of triangular gold nanoplates with and without surfactants is developed. The temperature profile in the microchannel, residence time and composition have been studied to understand effect of these parameters on the yield of the triangular nanoplates and were optimized for obtaining maximum yield of triangles. The flow synthesis approach has been demonstrated where the Br- ions can be supplied to the reaction mixture either from the surfactant viz. Cetyl trimethylammonium bromide (CTAB) or even from HBr. Apart from the Br- ions, the temperature gradient at the inlet of the continuous flow reactor is one of the key parameter that affects the yield of the triangular nanoplates. Finally we establish that with a right combination of the controlling parameters abetter yield of the Au nanotriangles by flow methods can be achieved even in the absence of surfactant. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Flow synthesis; microreactor; Nucleation kinetics; Surfactants

Nanocomposite of silver and thermo-associating polymer by a green route: a potential soft-hard material for controlled drug release - Gupta, Nivika R.; Bhagavatula L. V. Prasad; Gopinath, Chinnakonda S.; Badiger, Manohar V. (RSC Advances, 2014)
Major research efforts are continuously being made to look for alternative, environment friendly green chemicals for the synthesis of nanoparticles in place of conventional and hazardous reducing agents such as sodium borohydride and hydrazine. We report here on the synthesis and characterization of AgNPs using a thermo-associating polymer namely, carboxymethyl guar grafted poly(ethylene oxide-co-propylene oxide) [CMG-g-PEPO]. The polymer acts as both reducing agent as well as stabilizing/capping agent. The formation of AgNPs with polymer was confirmed by UV/Vis spectroscopy and the TEM images indicated the size of nanoparticles to be in the range of 10-20 nm. We also demonstrated the use of these nanoparticles in the controlled release of doxorubicin hydrochloride (Dox), an anticancer drug. The binding of Dox onto the polymer and AgNPs was investigated by XPS and Raman spectroscopy which indicates that a charge-transfer mechanism is operative between the Dox and polymer holding both the entities together. The first synthesis of AgNPs using non-toxic thermo-associating polymer and subsequent release of Dox with body temperature (37 degrees C) as a trigger is the highlight of the present work.

pH-Dependent single-step rapid synthesis of cuo and cu2o nanoparticles from the same precursor - Nikam, Arun V.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2014)
A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Field effect transistors based on CuO nanoparticles showed a hole mobility of 3.5 x 10(-2) cm(2) V-1 s(-1), making them a suitable candidate for energy-related applications. The effect of hydrazine vapor exposure on the IV-characteristics of CuO nanoparticles was also investigated. This revealed a decrease in source current with respect to time.

Synthesis and in situ observation of 3D super lattices of gold nanoparticles using oil-in-water emulsion - Dutta, Ankur; Chakraborty, Jayanta; Bhagavatula L. V. Prasad; Sahu, Puspanjali (Journal of Colloid and Interface Science, 2014)
In this work oil-in-water emulsion has been successfully used as a confined environment to grow 3D superlattices of gold nanoparticles. The superlattices were grown from 5 nm uniform gold nanoparticles using slow destabilization method. The confined environment was created by forming a stable emulsion where the gold colloid suspended in toluene was used as oil phase. Superlattices were also formed in bulk solution using the same slow destabilization method. A comparative study reveals that compact superlattices form more readily inside the emulsion drops as compared to bulk precipitation. The unstable colloid (in bulk or as emulsion) was aged for various periods at 5 degrees C to form more compact superlattices. The best superlattices with sharp corners are observed when the superlattices are formed inside the emulsion and aged for a month. Two key parameters, the incubation temperature and anti-solvent concentration, are optimized to obtain larger superlattices with sharp features. A new method is also demonstrated for in situ observation of superlattice formation using an optical microscope. 2014 Elsevier Inc. All rights reserved.
Keywords: 3D nanocrystal superlattices; In situ observation of superlattice formation; Monodisperse gold nanoparticles; Nanocrystal superlattices

Time and temperature effects on the digestive ripening of gold nanoparticles: is there a crossover from digestive ripening to ostwald ripening? - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Langmuir, 2014)
The effects of time and temperature on the gold nanoparticle sizes obtained by digestive ripening have been investigated. In digestive ripening, a polydisperse colloid, upon refluxing with a surface-active ligand in a solvent, gets converted to a nearly monodisperse one. In this study, a polydisperse gold nanoparticle system was heated in 4-tert-butyltoluene with hexadecanethiol at different temperatures, viz., 60, 90, 120, 150, and 180 degrees C for different time periods, and the trends in particle size variations were recorded. At lower temperatures such as 60 and 90 degrees C, after the initial narrowing of the size distribution, the particle sizes remain constant even though the refluxing step is continued for 24 h, substantiating the prevalence of the digestive ripening process. However, at elevated temperatures (120, 150, and 180 degrees C) particle sizes grow continuously, indicating a deviation from the digestive ripening behavior to an Ostwald ripening-type phenomenon.

Ultrathin sheets of metal or metal sulfide from molecularly thin sheets of metal thiolates in solution - Busupalli, Balanagulu; Kummara, Sreenivas; Kumaraswamy, Guruswamy; Bhagavatula L. V. Prasad (Chemistry of Materials, 2014)
Materials that exist as single molecule thick twodimensional sheets are in great demand because they hold promise as precursors for synthesis of layered functional materials. We demonstrate that metal thiolates, that exist as lamellar assemblies in the neat state, can be disassembled into individual molecular sheets simply by dilution in apolar organic solvents and that these can form ultrathin metallic layers on substrates upon heat treatment. We establish the pathway to the disassembly of metal thiolates in solution using a combination of techniques, including X-ray diffraction, light scattering, FTIR, and TEM. Our results indicate that the lamellar structure of Pd-thiolates is preserved in toluene up to a concentration of 300% w/v and the average intersheet distance is unchanged. Interestingly, the dynamics of the Pd-thiolate sheets remain correlated even on diluting them up to 30% w/v, though the disorder within the lamellar stacks increases with a decrease in their coherence length. Finally, at dilutions less than about 5% w/v, individual sheets of these structures can be accessed that are isolated and directly observed using TEM. Heat treatment of the ultrathin films of metal thiolates deposited on appropriate substrates resulted in the formation of metal or metal sulfides with retention of sheetlike morphologies.

Vesicle structures from bolaamphiphilic biosurfactants: experimental and molecular dynamics simulation studies on the effect of unsaturation on sophorolipid self-assemblies - Dhasaiyan, Prabhu; Pandey, Prithvi Raj; Visaveliya, Nikunjkumar; Roy, Sudip; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2014)
The formation of giant-vesicle-like structures by self-assembling linolenic acid sophorolipid (LNSL) molecules is revealed. Sophorolipids belong to the class of bolaamphiphilic glycolipid biosurfactants. Interestingly, the number of double bonds present in the hydrophobic core of sophorolipids is seen to have a great influence on the type of self-assembled structures formed. Dye encapsulation results establish the presence of an aqueous compartment inside the LNSL vesicles. Molecular dynamics simulation (MD) studies suggest the existence of two possible conformations of LNSLs inside the self-assembled structures and that LNSL molecules arrange in layered structures.
Keywords: bolaamphiphiles; MD simulations; Self-assembly; sophorolipids; vesicles

Preparation of Ag(Shell)-Au(Core) nanoparticles by anti-galvanic reactions: are capping agents the ``real heroes'' of reduction? - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2015)
The formation of Ag(shell)-Au(core) nanoparticles by the reduction of Ag+ ions on preformed Au NPs, mediated by the capping agents like dodecylamine is described. We clearly established that while monodisperse Ag(shell)-Au(core) structures can be formed in presence of weak surface binding ligands such as amines, strong binding ligands such as thiols, lead to formation of separate monometallic Au and Ag particles. Apart from highlighting the influence of metal-ligand binding strength on the formation of core-shell nanoparticle architectures, our study also provides an easy means to produce Ag( shell)-Au( core) structures. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag(shell)-Au(core) nanoparticles; Anti-Galvanic reactions

Preparation of Ni3S2 and Ni3S2-Ni nanosheets via solution based processes - Busupalli, Balanagulu; Date, Kalyani S.; Datar, Suwarna; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2015)
An easy and convenient preparation of nanometer-thick sheets of Ni3S2 and Ni3S2–Ni from solution processed molecularly thin sheets of Ni-thiolates is described. Both the Ni3S2 and Ni3S2–Ni possessed sheet-like morphologies and displayed room temperature ferromagnetic characteristics. The ferromagnetic nature of these samples was also confirmed by MFM studies, and AFM/TEM investigations substantiated the sheet-like morphology of the samples.

Simple method for the preparation of ultra-small palladium nanoparticles and their utilization for the hydrogenation of terminal alkyne groups to alkanes - Seth, Jhumur; Kona, Chandrababu Naidu; Das, Shyamsundar; Bhagavatula L. V. Prasad (Nanoscale, 2015)
A simple and convenient method for the preparation of ultra-small palladium nanoparticles (Pd-NPs) by a modified digestive ripening method is described. These nanoparticles catalyse the hydrogenation of the terminal alkyne groups to alkanes selectively, and show no effect on other labile protecting and internal alkyne or internal/external alkene groups present in the molecule.

Bromide ion mediated modification to digestive ripening process: preparation of ultra-small Pd, Pt, Rh and Ru nanoparticles - Seth, Jhumur; Bhagavatula L. V. Prasad (Nano Research, 2016)
Nanoparticles of catalytically important transition metals, such as Pd, Pt, Rh, and Ru have been prepared by the well-known “digestive ripening” (DR) and “modified digestive ripening” (mDR) methods. In the traditional DR process, a polydisperse colloidal dispersion is refluxed in the presence of a surface-active molecule, such as alkanethiol. The mDR method involved a small modification in the procedure, wherein refluxing was performed with an alkanethiol and a tetra-alkylammonium bromide surfactant. This minor modification led to a dramatic change in the final particle size distributions, giving access to nanoparticles in the <3 nm size regime; this was not possible with the traditional DR process. Bromide ions, which are present during refluxing, proved to be an important ingredient in the modification process. These bromide ions are revealed to act as etchants, resulting in ultra-small nanoparticles. All transition metal nanoparticles investigated displayed catalytic activity in the reduction reaction of p-nitro phenol. Pd nanoparticles, synthesized by a modified digestive ripening method, exhibited the best catalytic activity among the systems investigated.

H2S detection using low-cost SnO2 nano-particle Bi-layer OFETs - Surya, Sandeep G.; Ashwath, B. S. Narayan; Mishra, Sushma; Karthik, A. R. B.; Sastry, A. B.; Bhagavatula L. V. Prasad; Rangappa, Dinesh; Rao, V. Ramgopal (Sensors and Actuators B-Chemical, 2016)
In this article, a unique platform with an organic field-effect transistor (OFET) integrated with metal oxide nanoparticles for sensing of H2S gas is presented. Metal oxide nanoparticles such as SnO2 and ZnO synthesized using herbal techniques were used in the fabrication of OFETs using a bi-layer technique. The as -synthesized nanoparticles were characterized by Field Effect Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD) and UV-vis Spectroscopy (UV-vis) to establish the material properties. We showed that the SnO2 based OFETs displayed better response for H2S at room temperature (25 degrees C) compared to the OFETs fabricated with ZnO. The characterization of the sensors by using extracted electrical parameters like field-effect mobility ([1), On -Current (Ion), threshold voltage (VT) and saturation current (ID]) establish the fact that the SnO2 based OFETs detect H2S gas at room temperature. Plausible mechanisms explaining the H2S gas detection by bi-layer film were discussed. On the other hand, the sensitivity of these OFETs against other reducing gases was less. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: bi-layer; H2S detection; Metal-oxide; OFETs; Sensor

In situ electrochemical transformation of Ni3S2 and Ni3S2-Ni from sheets to nanodisks: towards efficient electrocatalysis for hydrogen evolution reaction (HER) - Busupalli, Balanagulu; Battu, Shateesh; Haram, Santosh K.; Bhagavatula L. V. Prasad (Chemistryselect, 2016)
Transition metal sulphides have been viewed as alternatives to platinum based electrocatalysts for HER. Herein, we report the preparation of Ni3S2 in conjunction with Ni in a novel nanosheet morphology and verified its performance for HER. During cyclic polarization, exotic morphological transformation of Ni-3 S-2-Ni from nanosheets to nanodisks has been noted. This change is accompanied with initial increase in over-potential that passed through maxima (similar to 100mV above the starting potential) and decreased to similar to 50mV below the starting value. Enhanced electrocatalytic activity due to the morphological changes from sheets to nanodisks has been attributed to the formation of more number of exposed edge-planes known to promote HER. Kinetic analysis based on Tafel slope displayed by this composite is comparable to that of Pt based catalysts.

Large reduction in the magnitude and thermal variation of Frank elastic constants in a gold nanorod/nematic composite - Madhuri, P. Lakshmi; Prasad, S. Krishna; Shinde, Pravin; Bhagavatula L. V. Prasad (Journal of Physics D: Applied Physics, 2016)
We report measurements of splay and bend Frank elastic constants in a composite comprising a nematic liquid crystal doped with a small concentration of sterically stabilized gold nanorods. The composite exhibits not only a large reduction in the magnitude of the threshold voltage for switching (Vth, 20%), as well as of the splay (K11, 40%) and bend (K33, 40%) elastic constants, but also presents an unprecedented feature: a substantial diminution in the temperature dependence of these parameters, almost to the point of becoming thermally invariant. This observation is significant because the electro-optic switching of liquid-crystal devices is largely controlled by the K11 and K33 elastic constants. Electrical conductivity measurements also show interesting behavior upon the inclusion of nanorods. Whereas the intrinsic Arrhenius behavior governing the temperature dependence is enhanced, the frequency dependence shows qualitative features of Jonscher’s universal model, albeit with a higher exponent. Further, photoisomerization of an azobenzene guest component provides an additional influence on the elastic constants. The results are discussed in terms of (a) the effect of the order parameter dependence seen from the viewpoint of an extended mean-field model,and (b) local order. The advantage of incorporating nanorods with photofunctionality is also pointed out.

Self- assembly of isomannide-based monoesters of C18-fatty acids and their cellular uptake studies - Dhasaiyan, Prabhu; Parekh, Nimisha; Reddy, T. Vijai Kumar; Rani, G. Sandhya; Devi, B. L. A. Prabhavathi; Bhagavatula L. V. Prasad (RSC Advances, 2016)
The self-assembling behavior of oleic, elaidic and stearic acid-isomannide glycolipids is revealed. Amongst these, oleic and elaidic acid-based isomannide lipids self-assembled to form microspheres which were efficiently taken up by cancer cell lines enabling their usage for drug delivery applications.

Silver nanoparticles: a new perspective in endodontic therapy - Jadhav, Rajashree; Bhide, Shrinivas; Bhagavatula L. V. Prasad; Kunchiraman, Bipinraj; Shimpi, Jayesh; Nandhini, Usha (OAB Journal, 2016)
Silver has been in use in medicine since time immemorial because of its antimicrobial properties. But due to the emergence of antibiotics the use of silver has been declined. Several pathogenic bacteria have developed resistance against various antibiotics. This has led to reemergence of silver. Recently nano science and nanotechnology are gaining tremendous popularity. The small size of nanoparticles provides larger surface area and hence increases the effectiveness of nanoparticles. Silver nanoparticles are used in medical and dental applications ranging from silver based wound dressings, silver coated medicinal devices like catheters, endotrachial tubes, bone cements, in gels, lotions, cosmetics, in dental restorative materials, endodontic cements, dental implants caries inhibitory agents, and in prosthesis. The purpose of this article is to discuss briefly the potential role of silver nano particles in endodontic therapy.

Structural insight into self assembly of sophorolipids: a molecular dynamics simulation study - Pandey, Prithvi Raj; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Roy, Sudip (Zeitschrift Fur Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2016)
Sophorolipids contain hydrophilic head groups at the ends of a long hydrophobic tail. As a result, sophorolipids can self assemble into variety of structures in water. Atomistic self assembly simulations of sophorolipids are performed in water. Two sophorolipids, oleic acid sophorolipid and linolenic acid sophorolipid, differing in number of double bonds in the hydrophobic tail are considered for this study. Long time self assembly simulations are performed considering 1 :3 lipid to water ratio by weight for both oleic and linolenic acid sophorolipids. In addition to 1 : 3 ratio, long time self assembly simulations are also performed with 1 : 1 and 1 : 2 ratios for linolenic acid sophorolipids. Distinctions in structural arrangements of sophorolipid molecules in the self assembled configuration for all the systems are investigated. The present study aims to provide structural insight into the different self assembled configurations of sophorolipids in water.
Keywords: MD Simulation; self assembly; sophorolipids; United Atom Force Field

OFET based H2S gas sensing among reducing and mining gases using green synthesis SnO2 - Surya, S. G.; Roy, S.; Ganne, B. S. P.; Pasam, D.; Sastry, A. B.; Bhagavatula L. V. Prasad (2016 3rd International Conference on Emerging Electronics, ICEE 2016, 2017)
In this paper we present detection of H2S gas using an organic field effect transistor (OFET) based sensor. A low-cost green synthesis process for SnO2 nanoparticles and bi-layer approach for device fabrication have been adopted to come up with the sensor. With the help of multiparameteric analysis, selectivity towards H2S gas was proved among other reducing and mining gases.

Self - assemblies of bolaamphiphilic molecules - Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad (Chemical Record, 2017)
The current buzzword in science and technology is self-assembly and molecular self-assembly is one of the most prominent fields as far as research in chemical and biological sciences is concerned. Generally, self-assembly of molecules occurs through weak non-covalent interactions like hydrogen bonding, π–π stacking, hydrophobic effects, etc. Inspired by many natural systems consisting of self-assembled structures, scientists have been trying to understand their formation and mimic such processes in the laboratory to create functional “smart” materials, which respond to temperature, light, pH, electromagnetic field, mechanical stress, and/or chemical stimuli. These responses are usually manifested as remarkable changes from the molecular (e. g., conformational state, hierarchical order) to the macroscopic level (e. g., shape, surface properties). Many molecules such as peptides, viruses, and surfactants are known to self-assemble into different structures. Among them, glycolipids are the new entries in the area of molecules that are being investigated for their self-assembly characteristics. Among the different classes of glycolipids like rhamnolipids and trehalose lipids, owing to their biological preparations and their structural novelty, sophorolipids (SLs) are evoking greater interest among researchers. Sophorolipids are a class of asymmetric bolas bearing COOH groups at one end and sophorose (dimeric glucose linked by an unusual β(1→2) linkage). The extreme membrane stability of Archaea, attributed to the membrane-spanning bolas (tetraether glycolipids), has inspired chemists to unravel the molecular designs that underpin the self-assembly of bolaamphiphilic molecules. Apart from these self-assembled structures, bolaamphiphiles find applications in many fields such as drug delivery, membrane mimicking, siRNA therapies, etc. The first part of this Personal Account presents some possible self-assembled structures of bolaamphiphiles and their mechanism of formation. The later part covers our work on one of the typical bolaamphiphiles known as sophorolipids.
Keywords: Bolaamphiphiles; gels; self-assembly; sophorolipids; vesicles

Accelerated in vitro model for occlusion of biliary stents: investigating the role played by dietary fibre - Surwase, Sachin; Balakrishnan, Harishankar; Acharya, Subrat K.; Makharia, Govind K.; Kumaraswamy, Guruswamy; Bhagavatula L. V. Prasad (BMJ Innovations, 2018)
ackground To develop a new accelerated in vitro model that has implications for investigating the mechanism of biliary stent occlusion and help in the development of new materials that can alleviate this problem. Methods We employ a combination of reconstituted animal bile, bacteria and cellulose fibres optimised to reproducibly generate accelerated occlusion of stents, and produce occlusions that closely mimic those found in clinical studies. Results Our model affords repeatable, highly accelerated occlusion (within 2–3 days, compared with between about a week to 2 months in previous models). Our results highlight the role of dietary fibre in blockage of stents and demonstrate their importance in the onset of occlusion. Conclusions This accelerated model may have implications for developing biliary stents with enhanced patency.

Generic and scalable method for the preparation of monodispersed metal sulfide nanocrystals with tunable optical properties - Bera, Abhijit; Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K.; Bhagavatula L. V. Prasad (Langmuir, 2018)
A rational synthetic method that produces monodisperse and air-stable metal sulfide colloidal quantum dots (CQDs) in organic nonpolar solvents using octyl dithiocarbamic acid (C(8)DTCA) as a sulfur source, is reported. The fast decomposition of metal-C(8)DTCA complexes in presence of primary amines is exploited to achieve this purpose. This novel technique is generic and can be applied to prepare diverse CQDs, like CdS, MnS, ZnS, SnS, and In2S3, including more useful and in-demand PbS CQDs and plasmonic nanocrystals of Cu2S. Based on several control reactions, it is postulated that the reaction involves the in situ formation of a metal-C(8)DTCA complex, which then reacts in situ with oleylamine at slightly elevated temperature to decompose into metal sulfide CQDs at a controlled rate, leading to the formation of the materials with good optical characteristics. Controlled sulfur precursor's reactivity and stoichiometric reaction between C(8)DTCA and metal salts affords high conversion yield and large-scale production of monodisperse CQDs. Tunable and desired crystal size could be achieved by controlling the precursor reactivity by changing the reaction temperature and reagent ratios. Finally, the photovoltaic devices fabricated from PbS CQDs displayed a power conversion efficiency of 4.64% that is comparable with the reported values of devices prepared with PbS CQDs synthesized by the standard methods.

Solvent-less solid state synthesis of dispersible metal and semiconducting metal sulfide nanocrystals - Bera, Abhijit; Busupalli, B.; Bhagavatula L. V. Prasad (ACS sustainable chem. eng, 2018)
Monolayer protected metal and metal sulfide nanocrystals (NCs) have mainly two constituents; the inorganic metal or metal chalcogenide complex as core and organic molecule as shell. Noticing that metal thiolates have these ingredients inbuilt in their structure, we investigated them as possible precursors for the preparation of monolayer protected metal and metal sulfide NCs via solid state grinding method. Accordingly silver and gold NCs have been prepared using a solvent less green approach, by the simple and convenient solid state grinding of the corresponding metal thiolate with sodium borohydride. Similarly, a large variety of uniform-sized semiconducting NCs of metal sulfides including PbS, CdS, ZnS, MnS, Ag2S, and CuS could also be synthesized by the same solid state route by grinding the metal thiolates with octyl dithiocarbamic acid (C8DTCA) and in some cases C8DTCA plus small amount of oleylamine as sulfur source. Interestingly, this simple technique could be used to prepare sub-3 nm NCs like Ag2S, PbS, and CuS which are otherwise difficult to prepare by the conventional high temperature solution routes also. Most gratifyingly, all these NCs, though were prepared by a solvent less grinding method, could be easily dispersed in nonpolar solvents as the preparation method ensued the formation of organic molecule capped NCs.

Wet chemical synthesis of metal oxide nanoparticles: a review - Nikam, A. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Crystengcomm, 2018)
Metal oxide nanoparticles are an important class of nanomaterials that have found several applications in science and technology. Through wet chemical synthesis, it is possible to achieve selective surface structures, phases, shapes, and sizes of metal oxide nanoparticles, leading to a set of desired properties. Wet chemical synthesis routes allow fine tuning of the reaction conditions (temperature, concentration of substrate, additives or surfactants, pH, etc.) to afford the desired nanomaterials. In this review article, we highlight recent developments in the wet chemical synthesis of metal oxide nanoparticles to provide great control over the quality of the obtained nanomaterials. The review critically evaluates the different wet chemical methods for scalable production of metal oxide nanoparticles to satisfy the growing industrial demand for nanomaterials. Special attention is paid to continuous flow synthesis of metal oxide nanoparticles.

Development of a smart scaffold for sequential cancer chemotherapy and tissue engineering - Sengupta, Poulomi; Agrawal, Vinay; Bhagavatula L. V. Prasad (ACS Omega, 2020)
The fabrication of a dual-functional drug-containing porous polymeric scaffold by layer-by-layer surface modification involving citrate-stabilized gold nanoparticles and cisplatin molecules is being reported. These scaffolds were characterized by electron microscopy and X-ray photoelectron spectroscopy. The capability of the scaffolds to release hydrated cisplatin in a slow and sustained manner over two days is established. Most importantly, the scaffolds turn nontoxic and cell-friendly after drug release, thus allowing the noncancerous fibroblast cells to adhere and proliferate (from 5000 cells to 16,000 cells in 6 days), becoming a potential solution toward an effective drug-carrying scaffold for volume-filling applications. The scaffold-mediated cancer cell killing and fibroblast cell proliferation were confirmed by fluorescence microscopy imaging, flow cytometry, and cell proliferation assays. We surmise that such a dual-purpose (drug-delivery and volume-filler) scaffold could help avoid the multiple surgical interventions needed for tumor surgery and cosmetic corrections. To the best of our knowledge, this is the first example of scaffolds with such a dual functionality which gets manifested in a sequential manner.

Influence of gold nanorods on the structure and photonic bandgap in a twist grain boundary phase with smectic C* blocks - Sahoo, Rajalaxmi; Rao, D. S. Shankar; Hiremath, Uma S.; Yelamaggad, V. C.; Shinde, Pravin; Bhagavatula L. V. Prasad; Prasad, S. Krishna (Journal of Molecular Liquids, 2020)
We describe the first report of the influence of gold nanorods (GNR) on the induced twist grain boundary smectic C* (TGBC*) phase in a binary mixture of achiral bent-core and chiral linear liquid crystals. The GNR concentration-dependent phase diagram of these nanocomposites shows that the thermal range of this twist grain boundary phase having smectic C* blocks phase increases by 50% for an intermediate composition compared to that for the host binary mixture without nanorods. The inclusion of the nanorods is seen to have substantial effect on the structural and photonic bandgap features of the TGBC* phase. For example, the helical periodidty gets altered in all the three dimensions: while those within the block undergo a huge increase, the one which is orthogonal to the blocks, shrinks. The spacing of the square grid pattern arising normal to the TGB helix direction increases for the nanocomposites getting even doubled for a certain composition, a feature evidenced by optical microscopy as well as optical diffraction. Xray diffraction clearly brings out the feature that the presence of GNR alters the thermal character of the transition between the TGBC* and the cholesteric phase. Quantitative analysis of the data indicates that the system would remain in the vicinity of a possible tricritical point, a behavior having wider ramifications to understand the underlying critical phenomenon. Based on the experimental observations, and capturing the essence of the reported adaptive defect core targeting mechanism we propose a model wherein GNRs get confined in the grain boundary region. This feature offers a potential to have periodic and anisotropic plasmonic structure arising out of the synergetic interactions between the metal nanorod and the twisted grain boundary structure. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: 3D photonic bandgap; Gold nanorods; Induced phase; TGBC* phase; Tricritical phenomena

Unraveling the role of excess ligand in nanoparticle pattern formation from an evaporatively dewetting nanofluid droplet - Bhattacharjee, Kaustav; Biswas, Korak; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2020)
Nanoparticle (NP) patterning on a solid surface via nanofluid droplet evaporation is one of the most fascinating topics of research. Quite intriguingly, though a dose of excess ligand has been invariably included in all of the experimental studies that resulted in large-area NP patterns, the role of this excess ligand has been addressed inadequately in the modeling studies carried out so far. Addressing this, we have conducted systematic studies by including excess ligand both in our experiments and modeling, and correlated the results with each other. For this, we prepared nearly monodispersed thiol-protected gold nanoparticle dispersion in toluene and added calculated amounts of excess thiol before drop-casting it onto a transmission electron microscopy (TEM) grid. Subsequently, upon solvent evaporation, the patterns formed were imaged using conventional electron microscopy and analyzed with customized image processing tools, to perform statistically significant measurements. Our study demonstrates the ability of soluble excess ligand to induce NP aggregation under nonequilibrium condition, leading to large-area monolayer formation. These experimental results were then rationalized by Monte Carlo simulations, based on a modified coarse-grained two-dimensional (2D) lattice-gas model. We found that excess ligand facilitates NP spinodal phase separation under nonequilibrium conditions, largely governed by the interplay between ligand-solvent and nanoparticle-ligand interactions. Using power spectrum density analysis, we clearly demonstrate that these spatial patterns have fractal surface characteristics due to persistent fractional Brownian motion within subdiffusion limit.

Disordered but efficient: understanding the role of structure and composition of the Co-Pt alloy on the electrocatalytic methanol oxidation reaction - Dalavi, Shankar B.; Agarwal, Sheena; Deshpande, Pooja; Joshi, Kavita; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2021)
A systematic investigation of the electrocatalytic Methanol Oxidation Reaction (MOR) was carried out using a model Co:Pt alloy system with different compositions and structural arrangements of the Co and Pt atoms. The structural variations with the same alloy composition included those with disordered arrangement of Co and Pt atoms in a face-centered cubic (fcc) lattice and ordered arrangements in face-centered tetragonal (fct) lattices. Our investigations clearly show that structures with disordered arrangements with Co:Pt atomic ratios near to 1:1 display better electrocatalytic efficiencies even when compared to pure Pt. These experimental findings were then rationalized by means of Density Functional Theory (DFT) calculations. Electronic level signatures in terms of charge transfer and relative shift in the peaks of the d band for surface metal atoms are proposed to be the reasons for the superior catalytic activity of a particular composition over the others. An increase in the number of inequivalent sites for methanol adsorption in disordered systems appears to result in better catalytic performance in comparison with ordered systems.